2005
DOI: 10.1200/jco.2005.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase III Study of Docetaxel Compared With Paclitaxel in Metastatic Breast Cancer

Abstract: Docetaxel was superior to paclitaxel in terms of OS and TTP. ORR was higher for docetaxel. Hematologic and nonhematologic toxicities occurred more frequently in the docetaxel group. The global quality-of-life scores were similar for both agents over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
337
4
14

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 500 publications
(368 citation statements)
references
References 34 publications
13
337
4
14
Order By: Relevance
“…As far as the first point is concerned, Jones et al [24] in a Phase III trial of standard schedule of paclitaxel versus docetaxel showed superiority for docetaxel in all clinical endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…As far as the first point is concerned, Jones et al [24] in a Phase III trial of standard schedule of paclitaxel versus docetaxel showed superiority for docetaxel in all clinical endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…For the treatment of palindromic and metastatc patients with late breast cancer, chemotherapy occupies an extreme important position. With the applications of the third generation chemotherapy drugs such as docetaxel (TXT) and the improvement of chemotherapy program, the effects of chemotherapy have been furtherly improved (Biganzoli et al, 2004;Jones et al, 2005). However, the choice of the patients, especially who failed to adjuvant chemotherapy with the application of taxane and anthracycline, on current clinical chemotherapy was still blind.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the Programme Adjuvant Cancer du Sein (PACS) 01 study, comparing FEC with FEC-Docetaxel (Doc), and Breast Cancer International Research Group (BCIRG) 001 study, comparing FAC with DocAC, have shown significant and relevant survival benefits for Doc [2]. In addition, Doc has been shown to increase OS in metastatic breast cancer compared with paclitaxel [16], while high-dose adjuvant FEC 100 improved OS compared with a conventionally dosed anthracycline regimen [17].…”
Section: Introductionmentioning
confidence: 99%